2020
DOI: 10.3390/agriculture10070265
|View full text |Cite
|
Sign up to set email alerts
|

Quality of New Potatoes (Solanum tuberosum L.) in Response to Plant Biostimulants Application

Abstract: Background: In sustainable crop production focusing on high-value products, biostimulants have been gaining increasing importance, thus the hypothesis that plant biostimulants could contribute to improving new potatoes quality; Methods: The effects of the seaweed extracts Bio­algeen S90 (Ascophyllum nodosum) and Kelpak SL (Ecklonia maxima), as well as the humic and fulvic acids in HumiPlant (leonardite extract) on the tuber quality of very early potato cultivars (‘Denar’, ‘Lord’, ‘Miłek’) were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 35 publications
0
6
0
2
Order By: Relevance
“…In contrast, Leonel et al [16] reported that potato tubers fertilized with increased P exhibited a lower concentration of total sugar contents. Wadas and Dziugieł [188] found that the use of plant biostimulant (the seaweed extracts Bio algeen S90 (Ascophyllum nodosum) and Kelpak SL (Ecklonia maxima), as well as humic and fulvic acids) had a significant effect on starch content in potato cultivars Denar, Lord, and Miłek tubers but did not affect the content of total sugars (glucose, fructose, and sucrose), monosaccharides (glucose and fructose), or sucrose. In contrast, Grze'skiewic et al [189] reported that the starch content of the potato tubers of the medium-early cultivar Muza was not affected by application of the Bio-algeen S90.…”
Section: Sugar and Starch Contents Of Potato Tubersmentioning
confidence: 99%
“…In contrast, Leonel et al [16] reported that potato tubers fertilized with increased P exhibited a lower concentration of total sugar contents. Wadas and Dziugieł [188] found that the use of plant biostimulant (the seaweed extracts Bio algeen S90 (Ascophyllum nodosum) and Kelpak SL (Ecklonia maxima), as well as humic and fulvic acids) had a significant effect on starch content in potato cultivars Denar, Lord, and Miłek tubers but did not affect the content of total sugars (glucose, fructose, and sucrose), monosaccharides (glucose and fructose), or sucrose. In contrast, Grze'skiewic et al [189] reported that the starch content of the potato tubers of the medium-early cultivar Muza was not affected by application of the Bio-algeen S90.…”
Section: Sugar and Starch Contents Of Potato Tubersmentioning
confidence: 99%
“…The application of the seaweed extracts Bio-algeen S90 (A. nodosum) and Kelpak SL (E. maxima), as well as the humic and fulvic acids in HumiPlant (leonardite extract) increased marketable tuber yield 75 days after planting (the end of June) of very early potato cultivars 'Denar', 'Lord', and 'Miłek', on average, by 2.15 t•ha −1 , but it did not affect the dry matter content in tubers, presented in earlier papers [29,30]. Increased tuber yield can be associated with a reduction in the content of some mineral elements in the tubers [2].…”
Section: Discussionmentioning
confidence: 87%
“…Solanum tuberosum Potato Enhanced the starch content in potato tubers. Bio-algeen S90 [130] Rebutia heliosa Cactus Increased plant height, suckers, vegetative and root weights, plant circumference, flower number, flower time, and seed germination significantly.…”
Section: Ane [129]mentioning
confidence: 99%